A MYB/bHLH complex regulates tissue‐specific anthocyanin biosynthesis in the inner pericarp of red‐centered kiwifruit Actinidia chinensis cv. Hongyang. (29th April 2019) - Wang, Lihuan; Tang, Wei; Hu, Yawen; Zhang, Yabin; Sun, Jiaqi; Guo, Xiuhong; Lu, Han; Yang, Ying; Fang, Congbing; Niu, Xiangli; Yue, Junyang; Fei, Zhangjun; et al.
Summary: Many Actinidia cultivars are characterized by anthocyanin accumulation, specifically in the inner pericarp, but the underlying regulatory mechanism remains elusive. Here we report two interacting transcription factors, AcMYB123 and AcbHLH42, that regulate tissue‐specific anthocyanin biosynthesis in the inner pericarp of Actinidia chinensis cv. Hongyang. Through transcriptome profiling analysis we identified five MYB and three bHLH transcription factors that were upregulated in the inner pericarp. We show that the combinatorial action of two of them, AcMYB123 and AcbHLH42, is required for activating promoters of AcANS and AcF3GT1 that encode the dedicated enzymes for anthocyanin biosynthesis. The presence of anthocyanin in the inner pericarp appears to be tightly associated with elevated expression of AcMYB123 and AcbHLH42 . RNA interference repression of AcMYB123, AcbHLH42, AcF3GT1 and AcANS in 'Hongyang' fruits resulted in significantly reduced anthocyanin biosynthesis. Using both transient assays in Nicotiana tabacum leaves or  Actinidia arguta fruits and stable transformation in Arabidopsis, we demonstrate that co‐expression of AcMYB123 and AcbHLH42 is a prerequisite for anthocyanin production by activating transcription of  AcF3GT1 and AcANS or the homologous genes. Phylogenetic analysis suggests that AcMYB123 or AcbHLH42 are closely related to TT2 or TT8, respectively, which determines proanthocyanidin biosynthesis in Arabidopsis, and to anthocyanin regulators in monocots rather than regulators in dicots. All these experimental results suggest that AcMYB123 and AcbHLH42 are the components involved in spatiotemporal regulation of anthocyanin biosynthesis specifically in the inner pericarp of kiwifruit. Significance Statement: AcMYB123 and AcbHLH42 are the components involved in spatiotemporal regulation of anthocyanin biosynthesis specifically in the inner pericarp of kiwifruit.